The theory of revenue pooling - Hellmuth St. Seidenfus (Intereconomics, 1973)
In ocean shipping effective competition cannot be expected without competitive controls as in this case the so called market mechanism frequently fails. The following article discusses the role of revenue pools in the system of organised competition in ocean shipping.
Keywords: 330; Shipping